Halogenated polyethersulfone sulfides - Kharaev A. M.; Bazheva R. Ch.; Borodulin A. S. (E3S Web of Conferences, 2023)
This paper presents the results of a study of random copolyethersulfone sulfides based on 4,4-dichlorodiphenylsulfone, 1,1-dichloro-2,2-di(4-hydroxyphenyl)ethylene, and sodium sulfide. The synthesis of copolyethersulfone sulfides with different ratios of polyethersulfone and polyphenylenesulfone sulfide units was carried out by high-temperature polycondensation by the reaction of nucleophilic substitution in N,N-dimethylacetamide medium and using potassium carbonate as an alkaline agent. The effect of the solvent used on the yield and reduced viscosity of polyethersulfone sulfides was studied. It has been shown that polymers with high reduced viscosity can be obtained in N,N-dimethylacetamide and N,N-dimethylformamide. The growth dynamics of the reduced viscosity of polyethersulfone sulfides was also studied depending on the ratio of sulfone and sulfide groups. The solubility of these polymers in various solvents has been studied.